Evaluasi Perkembangan Anak Usia Dini: Identifikasi Kesesuaian Tahap Perkembangan Dan Kebutuhan Intervensi - Zakiah Ulya; Asfi WE; Ainun Alkaff; Ririn Aryani (Universitas Muhammadiyah Metro, 2025)
This study aims to measure the development of kindergarten (TK) students across four main domains: fine motor skills, gross motor skills, language & speech, and social & independence, to determine whether students have achieved age-appropriate developmental milestones or require further support. The method used is a descriptive quantitative approach, with data collection through observation using the Early Childhood Developmental Detection (DDTK) instrument. The assessments were conducted individually by four observers who aligned their perceptions to ensure consistency in the measurement process. The results show that 5 students (38.5%) have development that aligns with their age milestones, 6 students (46.2%) fall into the questionable category, and 2 students (15.3%) show potential deviations from expected developmental stages. Among the developmental areas, the highest achievement percentages are found in the Social & Communication domain (93%), followed by Speech & Language (88%), Fine Motor Skills (71.5%), and Gross Motor Skills (65.4%). These results emphasize the importance of early detection and additional stimulation in the gross motor and speech & language domains to ensure optimal developmental outcomes for young children.